Regulatory Reconstruction of Waste Management to Achieve Efficient and Sustainable Environmental Management - Sidik, Moh.; Lisdiyono, Edy (International Journal of Criminology and Sociology, 2021)
One of the fundamental problems related to environmental management that continues to receive attention is waste. Likewise, waste management is still a serious problem faced by Pemalang, Central Java. This study seeks to discuss the reconstruction of waste management regulations in Pemalang Regency, Central Java, Indonesia. The results showed that the prevailing regulation is suboptimal and inefficient due to the presence of two concurrent waste management sectors, i.e., public work and environmental department. Besides, the community’s low participation at the village level also hinders waste management. Therefore, waste management regulation reconstruction is necessary to address the issues of waste management in Pemalang Regency. The results of the present study highlight the legal aspects and demonstrated the reconstruction of the waste management regulation in Pemalang Regency to obtain sustainable and efficient environmental management. The result of the study showed that waste management could be optimized by focusing on one sector, i.e., the environmental department. In addition, the subdistrict or village government should be given the authority to participate in managing waste, which will create a synergy between the government and the community.